Vocabulary Development and Trajectories of Behavioral and Emotional Difficulties Via Academic Ability and Peer Problems. Issue 2 (29th January 2019) - Westrupp, Elizabeth M.; Reilly, Sheena; McKean, Cristina; Law, James; Mensah, Fiona; Nicholson, Jan M.
Abstract : This study investigates associations between trajectories of children's vocabulary development and subsequent behavioral and emotional difficulties via two potential mediating mechanisms; literacy and peer problems. Nationally representative data from 4, 983 Australian children were used to examine trajectories of receptive vocabulary (4–5, 6–7, and 8–9 years) and hyperactivity‐inattention, conduct problems and emotional symptoms (8–9, 10–11, 12–13, 14–15 years), and literacy and peer problems (8–9 years). Lower growth in vocabulary was related to trajectories of hyperactivity‐inattention, conduct problems, and emotional symptoms. Literacy was a key mediator explaining these associations. Results were consistent for children below the 50th percentile for vocabulary at 4–5 years compared to the full sample. These findings suggest that early literacy‐based interventions may alleviate declining academic, emotional and behavioral functioning in adolescence.